Micropropagação de mangabeira (Hancornia speciosa Gomes) de diferentes variedades botânicas - Belo, Emiliane dos Santos (2023)
The mangabeira - Hancornia speciosa Gomes (Apocynaceae) is a fruit tree typical of the Brazilian Cerrado, whose fruits are consumed and sold locally, making it a genetic resource of great cultural, economic, and environmental importance. The primary method of obtaining the fruits is through local extraction, highlighting the urgent need to conserve its natural populations to prevent genetic erosion and threats to the species. Naturally distributed throughout Brazil, the mangabeira produces recalcitrant seeds with rapid viability loss, making long-term conservation unfeasible. Thus, germplasm collections are essential for the conservation and rescue of native germplasm, as well as providing support for breeding strategies. Vegetative propagation or cloning is recommended for species improvement, as it prevents segregation and fixes desirable agronomic traits of superior matrices. Micropropagation emerges as an effective alternative, allowing the rescue and storage of in vitro germplasm, contributing to the elucidation of in vitro responses of botanical varieties and the cloning and multiplication of promising genotypes. However, most reports on micropropagation describe only H. speciosa, without addressing the botanical variety, which complicates breeding and conservation efforts. Given the need for specific protocols, the general objective of this study was to evaluate the effect of different plant growth regulators on the micropropagation of three botanical varieties of mangabeira from the germplasm collection of the School of Agronomy at UFG. Initially, the effects of different culture media for the germination and rescue of embryos of the varieties gardneri, cuyabensis, and pubescens were evaluated. It was observed that the cuyabensis and gardneri varieties showed better survival in seed-germinated plants, while the pubescens variety performed better in embryo rescue plants. The WPM medium was satisfactory for germination of all botanical varieties. Regarding growth, the pubescens and gardneri varieties showed better development in the absence of sucrose or with 15 g.L-1, both for embryo rescue plants and seed-germinated plants. The cuyabensis variety, on the other hand, had better growth of embryo rescue plants in WPM medium with up to 45 g.L-1 of sucrose. In the study of shoot multiplication of in vitro germinated plants, the budding of the varieties was tested with different cytokinins, with BAP at doses up to 4.4 μM being the best cytokinin for all botanical varieties. For the rooting of in vitro shoots, different auxins were tested, revealing that rooting was higher in the absence of auxins. The in vitro rooted plants were acclimatized in different substrates in a greenhouse, with the survival of the gardneri and pubescens varieties being better in sand and vermiculite (1:1), while for the cuyabensis variety, the composite substrate proved to be more suitable.